Incapacidade no pós acidente vascular cerebral no Brasil: análise populacional da limitação em atividade e restrição no acesso aos serviços de saúde - Silva, Luana Karoline Castro (2023)
The high incidence of stroke suggests that reducing the global burden of stroke is urgent. Studies that investigate the prevalence of stroke, disability and access to post-stroke health services, including rehabilitation with physiotherapy in the country and its regions, as well as knowing the factors associated with the use of physiotherapy services by people poststroke. Stroke residents in Brazil will be able to help understand the regional distribution of stroke, its functional impact and how to promote access to healthcare by region of the country. For this purpose, in this dissertation, two products were developed. The first product consisted of estimating the prevalence of self-reported stroke and the degrees of limitation in usual activities, the prevalence of access to health services and the proportion between limitation in usual activities and access to physiotherapeutic treatment by post-stroke people in the five regions from the country. To this end, a cross-sectional study was conducted with data from the 2019 National Health Survey (NHS), which included individuals from the five geographic regions of Brazil aged 18 years or over who reported a diagnosis of stroke. In this study, a stroke prevalence of 1.9% in Brazil was concluded, equivalent to 1975 individuals who reported a stroke diagnosis. Of these, the majority reported functional limitations and regular follow-up with a health professional, but only 24.6% reported access to rehabilitation. Furthermore, 73.4% of individuals who reported some limitation in activity were without physiotherapeutic treatment, illustrating the inequity of stroke and the assistance offered in Brazil. The second product aimed to estimate, based on a statistical model, the factors associated with the use of physiotherapy services after stroke in Brazil, based on Andersen's Behavioral Model of Use of Health Services. This was a population-based cross-sectional study with data from the 2019 NHS, which performed a logistic regression analysis to determine the outcome of post-stroke physiotherapy service use (dependent variable). The independent variables were selected based on the theoretical model, consisting of nine variables included in the components characteristics of the population, environment and health behavior. In the multivariate analysis, the population characteristics component, with self-perception of functional limitation, represented by individuals who reported having stopped performing some of their usual activities in the last two weeks, and the health behavior component, represented by post-stroke self-care (following a diet, regular use of medication and use of other rehabilitation services) also maintained an association to use the physiotherapy service. Finally, this dissertation presents studies with unprecedented results, which contribute to expanding the understanding of the stroke panorama in Brazil in coherence with the demands highlighted by the WHO in facing the global burden 13 of stroke, responding to the pillars of stroke surveillance, rehabilitation at a population level and considering research priorities for the evolution of the physiotherapy profession. This demonstrates the importance of analyzing and publishing these results about disability and post stroke health systems, which includes rehabilitation, based on population data.